Global and regional burden of pneumoconiosis, 1990–2021: an analysis of data from the global burden of disease study 2021 - Chen, Ye; Liu, Dandan; Ji, Huixia; Li, Wenying; Tang, Yuhua (Frontiers in Medicine, 2025)
BackgroundPneumoconiosis remains a widespread occupational disease globally. This study provides an updated overview of the global burden of pneumoconiosis, examining incidence and mortality from 1990 to 2021.MethodsThe study assessed the incidence and mortality of pneumoconiosis using GBD data from 1990 to 2021, presenting findings as point estimates with 95% uncertainty intervals.ResultsIn 2021, there were 62,866 new pneumoconiosis cases and 18,323 deaths worldwide, with age-standardized incidence (ASIR) and age-standardized mortality rates (ASMR) of 0.736 and 0.219 per 100,000 population, respectively, showing decreases of 28.5 and 52.8% since 1990. The highest ASIR and ASMR of pneumoconiosis were found in middle and high-middle SDI quintiles in 2021, with East Asia having the highest ASIRs. ASIR and ASMR generally declined but rose in Australasia and Oceania from 1990 to 2021. Globally, the number of incidences peaked at 65–69 years in 1990 and 2021, with death peaks at 65–69 years in 1990 and 80–84 years in 2021. A correlation analysis revealed that ASIR and ASMR either decreased or remained stable in the majority of countries and territories as SDI increased. Decomposition analysis shows that population growth and aging drove the global number increase in most regions, while epidemiological changes had a negative impact.ConclusionDespite an overall decline in global pneumoconiosis burden from 1990 to 2021, particularly in the middle and high-middle SDI quintiles, and in East Asia. The future looks promising, but pneumoconiosis remains a public health concern. The implementation of prevention strategies and improving the quality of life of current patients should be a priority.